THE POWER OF BODY LANGUAGE IN HUMAN COMMUNICATION - Toshmirzayeva Sitora; To'raqulova Sobira; Sattorova Sabohat (TADQIQOTLAR, 2025)
Abstract This article explores the significance of body language in human communication. It investigates how non-verbal cues, including facial expressions, gestures, eye contact, and posture, contribute to the communication process. By examining both universal and culture-specific body language, this paper explains the advantages of understanding non-verbal signals and their practical applications in everyday and cross-cultural contexts.